Pengaruh Audit Manajemen dan Pengendalian Intern Terhadap Penerapan Good Corporate Governance dan Implikasinya Terhadap Kinerja Perusahaan di Indonesia (Studi Empiris Pada 141 Perusahaan BUMN dalam Daftar CGPI yang Dirilis IICG Periode 2008-2013) - Amelia Oktrivina Diapari Siregar (Jurnal Keuangan dan Perbankan, 2014)
The implementation of Good Corporate Governance (GCG) principles on the State-owned companies has already shown increased. Nevertheless from several public view is still much stigma which the companies still laden with corruption and loss. The main objective of this study was to determine whether the management audit, internal control and application of the GCG principles affect the performance of state-owned companies . This study used a survey method using SEM analysis approach. The results showed that the management audit after on GCG has shown a lot of improvement . Similarly, the effect of internal control over the practice of good corporate governance has got a good assessment. The latter effect of corporate governance on corporates performance is viewed positively significant. Therefore , the importance of GCG implementation, the existence of audit committees and internal controls